Genetic predisposition to an impaired metabolism of the branched chain amino acids and risk of type 2 diabetes: A Mendelian randomisation analysis - Lotta, L; Scott, R; Sharp, S; Burgess, S; Luan, J; Tillin, T; Schmidt, A; Imamura, F; Stewart, I; Perry, J; Marney, L; Koulman, A; et al. (Public Library of Science, 2016)
Background: Higher circulating levels of the branched chain amino acids (BCAA; i.e. isoleucine, leucine and valine) are strongly associated with higher type 2 diabetes risk, but it is not known whether this association is causal. We undertook large-scale human genetic analyses to address this question. Methods, findings and limitations: Genome-wide studies of BCAA levels in 16,596 individuals revealed five genomic regions associated at genome-wide levels of significance (p<5 x 10-08). The strongest signal was 21kb upstream of the PPM1K gene (beta in standard deviations of leucine per allele=0.08; p=3.9 x 10-25), encoding an activator of the mitochondrial branched-chain alpha-ketoacid dehydrogenase (BCKD) responsible for the rate-limiting step in BCAA catabolism. In up to 47,877 cases of type 2 diabetes and 267,694 controls, a genetically-predicted difference of 1 standard deviation in amino acid levels was associated with an odds ratio of type 2 diabetes of 1.44 (95% confidence interval, 1.26-1.65, p=9.5 x 10-08) for isoleucine, 1.85 (1.41-2.42, p=7.3 x 10-06) for leucine and 1.54 (1.28-1.84, p=4.2 x 10-06) for valine. Estimates were highly consistent with those from prospective observational studies of the association between BCAA levels and incident type 2 diabetes in a meta-analysis of 1,992 cases and 4,319 non-cases. Metabolome-wide association analyses of BCAA-raising alleles revealed high specificity to the BCAA pathway and an accumulation of metabolites upstream of branched-chain alpha-ketoacid oxydation, consistent with reduced BCKD activity. Limitations of this study are that, while the association of genetic variants appeared highly specific, the possibility of pleiotropic associations cannot be entirely excluded. Similar to other complex phenotypes, genetic scores used in the study captured a limited proportion of the heritability in BCAA levels. Therefore, it is possible that only some of the mechanisms that increase BCAA levels or affect their metabolism are implicated in type 2 diabetes. Conclusions: Evidence from this large-scale human genetic and metabolomic study is consistent with a causal role of BCAA metabolism in the aetiology of type 2 diabetes.